Histopathological aspects of mango resistance to the infection process of Ceratocystis fimbriata. (27th March 2014) - Araujo, L.; Silva Bispo, W. M.; Cacique, I. S.; Cruz, M. F. A.; Rodrigues, F. A.
<x xml:space="preserve">Abstract</x> Mango wilt, caused by Ceratocystis fimbriata, is one of the most important diseases affecting mango yields in Brazil. Information regarding the infection process of C. fimbriata in the stem tissues of mango from different cultivars and the basis of host resistance to the pathogen is rare in the literature. Thus, the objective of the study was to investigate how infection by two isolates of C. fimbriata can be affected by mango cultivar‐specific mechanisms of resistance. Disease progress on the inoculated stem tissues of the mango cultivars was evaluated and stem sections were obtained from the site of inoculation and prepared for histopathological observations using light microscopy. The factors mango cultivars and C. fimbriata isolates and their interaction were significant for all measures of disease development. Plants from the cultivars Espada, Haden and Palmer inoculated with isolates of C. fimbriata were more susceptible, whereas plants from the cultivars Tommy and Ubá were moderately resistant and resistant, respectively. Histopathologically, fungal isolates apparently massively colonized the stem tissues of plants from the susceptible cultivars Espada, Haden and Palmer, starting from the collenchyma and moving in the direction of the cortical parenchyma, xylem vessels and pith parenchyma. By contrast, on stem tissues of plants from the resistant cultivars Tommy Atkins and Ubá, most of the cells reacted to C. fimbriata infection by accumulating amorphous material. The results from the present study strongly indicated the importance of phenolic compounds for mango cultivar resistance against infection by Brazilian C. fimbriata isolates.